2009
DOI: 10.1897/08-069.1
|View full text |Cite
|
Sign up to set email alerts
|

Single‐ and two‐species tests to study effects of the anthelmintics ivermectin and morantel and the coccidiostatic monensin on soil invertebrates

Abstract: Soil invertebrates in arable land are potentially exposed to veterinary medicines excreted by husbandry. The toxicity of three widely used pharmaceuticals was therefore investigated with the use of common soil invertebrates exposed in the laboratory in single- or two-species test system. The anthelmintic morantel did not cause significant mortality to either Folsomia fimetaria or Enchytraeus crypticus even at the highest tested concentration of 900 mg kg(-1) dry soil. The coccidiostatic monensin affected the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…These interpolated EC50 values from the TME study were with 0.12-0.22 mg/ kg soil dw at the lower range of EC50 values determined in a SMS test system, a gnotobiotic microcosm (Jensen, personal communication). In a similar test with only two species, F. fimetaria and H. aculeifer, the EC10 for the collembolan was even lower (0.02 mg ivermectin/kg soil dw; Jensen et al 2009). It can be concluded that collembolans are the most sensitive soil organisms for ivermectin tested so far.…”
Section: Methodsmentioning
confidence: 89%
“…These interpolated EC50 values from the TME study were with 0.12-0.22 mg/ kg soil dw at the lower range of EC50 values determined in a SMS test system, a gnotobiotic microcosm (Jensen, personal communication). In a similar test with only two species, F. fimetaria and H. aculeifer, the EC10 for the collembolan was even lower (0.02 mg ivermectin/kg soil dw; Jensen et al 2009). It can be concluded that collembolans are the most sensitive soil organisms for ivermectin tested so far.…”
Section: Methodsmentioning
confidence: 89%
“…The tests revealed a high sensitivity of the collembolan F. candida to IVM as shown by a NOEC of 0.3 mg kg -1 soil (d.w.). Very similar results were found in another collembolan species, Folsomia fimetaria, with NOEC of 0.3 [207] and 0.4 mg kg -1 soil d.w. [208], with an ACR between LC 50 and NOEC with F. fimetaria of about 28 [197] and 13 [208]. …”
Section: Ecotoxicity Of Avermectinsmentioning
confidence: 99%
“…One of the worldwide used pesticides are the veterinary medicinal products to treat diseases, protect animal health, enhance productivity and promote growth (Jensen et al 2009). …”
Section: The Hazards and Risks Of Pesticide: From Individuals To Ecosmentioning
confidence: 99%
“…A possible explanation could be the preference and availability of hemi-euedaphic prey as observed by , in this case mainly F. fimetaria. Jensen et al (2009) reported the predatory-prey interactions between these two species and reported the influence response of test organisms to toxic substances. Although, the predatory mites were affected by all the exposure concentrations with a few extracted animals.…”
Section: Sms Test Systemmentioning
confidence: 99%
See 1 more Smart Citation